Analysis of approaches to the use of intermediate crops as feedstock for biomethane production in Ukraine - Zheliezna Т.; Drahniev, S. (Energy and Automation, 2024)
The wide use of renewable energy sources, in particular biomass, makes a significant contribution to the decarbonization of the energy and transport sectors. Today, one of the most promising directions for the development of European and Ukrainian bioenergy is the production and consumption of biomethane. Biomethane can be used both, as a direct substitute for natural gas in the production of heat and electricity, and as motor fuel. The priority development of biogas/biomethane production is indicated in the European Green Deal, which the EU has been following since the end of 2019. Special attention is paid to the issues of sustainable development of bioenergy, including the use of sustainable feedstock for obtaining all types of biofuels. Because of this, the new version of the EU Renewable Energy Directive of 2023 (RED III) strengthened the sustainability requirements for the production of liquid biofuels and biogas for transport. One of the sustainable types of feedstocks for the production of biomethane can be biomass of intermediate crops, which are plants that are grown in the time interval free from the cultivation of main crops in the crop rotation. All the mentioned issues are relevant and important for Ukraine as a member of the Energy Community and a potential member of the EU, which will join the implementation of the European Green Deal in the future. The purpose of the work is to assess the potential of biomethane production from intermediate crops in Ukraine and to develop some preliminary recommendations for the development of this sector. The assessment of the potential was carried out using the conservative approach described in the study by experts of Ghent University (Belgium). It is assumed that 20% of the total sown area can be allocated for the cultivation of intermediate crops. The obtained results show that even with a conservative approach, the potential for biomethane production from intermediate crops is the largest component of the total potential for obtaining biomethane from various feedstocks in Ukraine, namely 9.29 billion m3 CH4/y, which is 47% of the total potential. This points to very good prospects for the development of this bioenergy sector in the country. When elaborating preliminary recommendations for the introduction of biomethane production from intermediate crops in Ukraine, main principles of Biogasdoneright, the European model of sustainable agriculture development were taken into account. Ukraine’s natural-climatic and soil-water conditions have been analysed from the viewpoint of possibility and effectiveness of growing intermediate crops for bioenergy. Some types of agricultural crops for sequential cultivation and possible crop rotations have been suggested. The directions of further research, scientific and practical work necessary for the development of this bioenergy sector in Ukraine have been determined. Key words: intermediate crops, bioenergy, biomass, biogas, biomethane